Enhancing geometry learning through project-based teaching materials: A focus on circumference and area of circles - Sari, Lili Nur Indah; Hoiriyah, Diyah (Mahesa Research Center, 2024)
This study aims to develop a Student Worksheet based on the Project-Based Learning (PjBL) approach, ensuring its validity, practicality, and effectiveness in facilitating mathematics instruction on the topic of circumference and area of circles for MTs students. The research follows a Research and Development (R&D) methodology, employing the ADDIE development model, which encompasses five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation process assessed the worksheet’s quality across four aspects: content feasibility, material presentation, worksheet structure, and linguistic quality. The results indicate that the content feasibility scored 84%, material presentation 86.5%, worksheet elements 86%, and linguistic quality 88%, all within the “very valid” category. Overall, the Student Worksheet achieved a validity score of 86% (categorized as “very valid”), confirming its appropriateness for use in the classroom. These findings suggest that the PjBL-based Student Worksheet effectively supports mathematics learning and meets expert criteria for validity.